Mamíferos quaternários de Itapipoca, Ceará, Brasil, depositados no Museu Nacional, Rio de Janeiro - Mello, Marcia Gomide da Silva (1990)
In this work we intended to review and organize the pleistocenic mammals material found inside tanks, in Itapipoca city, Ceará state. Nowadays, those fossils are included in the vertebrate Paleontological Collection of Museu Nacional, Rio de Janeiro. After the revision, we identified 14 species, 1 genus and 1 tribe, belonging to 12 families and 5 orders. Here are identified taxa: Northotherium maquinense, Xenocus cearensis, Eremothrium laurillardi, Scelidodon cuvieri, Holmesina paulacoutoi, Glyptodon sp., Cerdocyon thous, Protocyon troglodytes, Smilodon populator, Haplomastodon waringi, Hippidion principale, Equus (Amerhippus) neogaeus, Tayassu pecari, Palaeolama major, Mazama gouazubira, Ozotoceros bezoarticus, Odocoileini, Cingulata, Edentata, Artiodactyla an Mammalia. These extinct groups are similar to those of other northeastern states of Brasil except x. cearensis, which has only been found in Ceará state. Based on such fauna we concluded that demi-humid climate and savannah vegetation found in Ceará state, doring the Pleistocene, do not exist there anymore. Analysing the hipothesis that try to explain the presence of these fossils remains inside Itapipoca tanks, we picked out two of them possible to occur ; some animals slipped into these tanks while looking for water, and could not go out; Others died in the surroundings and thair remains were carried into the tanks by flood.